2020
DOI: 10.1111/wrr.12814
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory effects of haptoglobin on LPS‐stimulated macrophages: Role of HMGB1 signaling and implications in chronic wound healing

Abstract: Nonhealing wounds possess elevated numbers of pro-inflammatory M1 macrophages, which fail to transition to anti-inflammatory M2 phenotypes that promote healing. Hemoglobin (Hb) and haptoglobin (Hp) proteins, when complexed (Hb-Hp), can elicit M2-like macrophages through the heme oxygenase-1 (HO-1) pathway. Despite the fact that nonhealing wounds are chronically inflamed, previous studies have focused on non-inflammatory systems, and do not thoroughly compare the effects of complexed vs individual proteins. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 38 publications
0
17
1
Order By: Relevance
“…LC-MS/MS protein analysis of this liquid demonstrated a significant increase in haptoglobin and thrombospondin-4 in the TGM-treated wounds (Fig. S3b, c), which are known to influence macrophage differentiation and epithelial cell migration, respectively ( 41-44 ). Collectively these studies showed that TGM significantly enhances the rate of wound closure with increases in serous volume and concentrations of factors associated with augmented wound healing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…LC-MS/MS protein analysis of this liquid demonstrated a significant increase in haptoglobin and thrombospondin-4 in the TGM-treated wounds (Fig. S3b, c), which are known to influence macrophage differentiation and epithelial cell migration, respectively ( 41-44 ). Collectively these studies showed that TGM significantly enhances the rate of wound closure with increases in serous volume and concentrations of factors associated with augmented wound healing.…”
Section: Resultsmentioning
confidence: 99%
“…The mice were maintained in a pathogen-free facility at the Rutgers New Jersey Medical School Comparative Medicine Resources. The wound healing studies used a revised protocol based upon a standard procedure ( 35, 41 ). Briefly, two days prior to the wounding, the mice were anesthetized with a rodent cocktail containing Ketamine (80mg/kg) and Xylazine (10mg/kg) and their dorsal skin was shaved followed by a depilatory cream (Nair) to further remove hair.…”
Section: Methodsmentioning
confidence: 99%
“…To date, M1 (pro‐inflammatory or classic), M2 (pro‐healing or alternative), which comprises three subtypes M2a, M2b, M2c, and M1/M2 hybrid, are proved to be the main macrophage phenotypes in the wound microenvironment 19 . Being stimulated by PAMP and DAMP molecules, M1 is the preliminary phenotype appearing in the skin wound zone and secreting pro‐inflammatory and inflammatory mediators like nitric oxide synthase 2 (NOS2), IL1β, IL6, IL8, IL12, tumor necrosis factor α (TNFα), matrix metallopeptidase 2 (MMP2), MMP9 19,20 . As normal healing carries on, M1 to M2 transition occurs, and the M2/M1 ratio rises.…”
Section: Introductionmentioning
confidence: 99%
“…M2 phenotype is induced by IL4 and IL13 19 and provokes angiogenesis, collagen degradation, remodeling, cell proliferation, and differentiation initiation; these are key contributors to healing. M2 macrophages trigger all these events by secreting growth factors such as platelet‐derived growth factor (PDGF), 19 insulin‐like growth factor (IGF1), vascular endothelial growth factor (VEGF), TGFβ1 21,22 and other anti‐inflammatory molecules like IL10, 20 arginase1, 23 TIMP metallopeptidase inhibitor 1 (TIMP1) and cluster of differentiation 206 (CD206), 24 higher levels of CD206, CD163 are the main presenters of M2 like macrophages abundance 24,25 . The decline in M1 to M2 switch makes for an elongated inflammatory stage (which shifts acute wounds to chronic ones), definitely due to excessive M1 inflammatory cytokines and insufficient M2 anti‐inflammatory mediators 25 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation